Reversed Myth and Negative Symbols of Narcissus in Mother-Son Relationship in Hayashi Fumiko’s Narcissus - Ratna Asmarani (IZUMI, 2021)
The famous myth of Narcissus is about a mythical handsome young man who indifferently rejects the love of the nymph Echo leading to Echo’s broken heart and untimely death and his being cursed to excessively adore his own handsome reflection on the pond till his death. The short story entitled Narcissus written by Hayashi Fumiko is intriguing because its title calls to mind the famous myth of Narcissus. However, this short story portrays the myth of Narcissus from a unique perspective. Thus, the aims of this paper are to analyse the reversed myth and negative symbols of Narcissus as reflected in the mother-son relationship in the short story. To support the analysis various psychological understandings of the myth of Narcissus are used as well as various understandings of the symbols of the flowers called Narcissus. The methods of research used are a comprehensive combination of textual-contextual methods as well as library research and qualitative research. The textual method focuses on the intrinsic aspects relevant to the focus of analysis, such as character, conflict, and setting, while the contextual method borrows the psychological concepts of the term Narcissus and the symbolic meaning of the flowers named Narcissus. The result shows that the mother-son relationship clearly portrays the reversed myth in the matter of the gender roles, the type of relationship, and the ending of the relationship. Another result shows that all the symbols related to the flowers of Narcissus turn into negative meanings in the sort of story entitled Narcissus by Hayashi Fumiko. In short, the short story writer turns upside down both the myth and the symbols resulting in an engaging story full of hidden meanings to be interpreted